GUIDANCE FOR VILLAGE OFFICIALS IN IMPLEMENTING BUSINESS COMPLIANCE, MANAGEMENT COMPLIANCE, AND COMPLIANCE IN IMPLEMENTING CONSTRUCTION SERVICES IN MOJOKERTO REGENCY - Adik Rudiyanto; Hafizh Fianto Putra; Wuwuh Asrining Puri (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2025)
Village-level construction project management in Indonesia faces significant challenges in applying construction service regulations mandated by Undang-Undang Nomor 2 Tahun 2017. This community service program addressed this gap by strengthening the capacity of village officials in Mojokerto Regency to understand and implement business compliance, management compliance, and construction service implementation standards. The program employed an integrated methodology combining training sessions, interactive workshops, practical simulations, and field assistance, engaging eighty-eight officials from villages across the regency. Pre-test assessments revealed limited baseline knowledge, with participants averaging 42.4% comprehension of regulatory requirements. Following the intervention, post-test results demonstrated substantial improvement to 86.2%, with the most significant gains observed in business compliance (38.2% to 84.5%). Participants successfully identified administrative and technical requirements in procurement processes and recognized the critical importance of systematic construction work monitoring. Field assistance in selected villages yielded tangible improvements in documentation practices and oversight functions. This initiative contributes meaningfully to enhanced governance practices, reduced financial irregularities, and accountable, high-quality village infrastructure development aligned with decentralization objective